Rice in the global economy : (International Rice Research Institute, 2010)
This book presents such a new vision for the future of rice farming. The book is foward-looking and addresses the key strategic questions in the context of major developments in the global economy. The various schoarly contributions in this book examine these strategic questions and lay out a rich menu of options for sustainably improving rice systems and enhancing the overall performance of the global rice economy to reduce poverty and hunger.